Modernity and authenticity a study in the social and ethical thought of Jean-Jacques Rousseau - Ferrara, Alessandro 1953-
"Study examines class, race, and gender in literature,concentrating on 1950s. Offers comparison with European writers, which helps to illuminate our understanding of Julieta Campos, Luisa Valenzuela, Cristina Peri Rosi, Helena Perente Cunha, Rigoberta Menchú, Domitila Barrios, and Carolina María de Jesus"--Handbook of Latin American Studies, v. 58.|uhttp://www.loc.gov/hlas